Análise proteômica sugere adaptação do músculo gastrocnêmio de camundongos com diabetes tipo II induzida por estreptozotocina e dieta hiperlipídica - Rodrigues, Chelsea Maria Vilas Boas Feitosa [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Type II diabetes mellitus is the most common, its prevalence has reached increasing global levels that demand a high economic expense and increase the propensity to vascular, cardiac and muscular diseases. In this scenario, proteomics has the potential to provide information about metabolic changes in carriers by identifying pathways and possible markers involved. Thus, the objective of this work was to analyze the proteomic profile of the gastrocnemius muscle of mice induced with type 2 diabetes to identify alterations and the influence of the high-fat diet. Eighteen adult male mice were divided into 3 experimental groups (n=6/group) namely: non-diabetic control (CND), streptozotocin-induced diabetic (CDD) and streptozotocin-induced diabetic and high-fat diet (DHL), they received 8 weeks high-fat diet (DHL group) or normocaloric diet (CND and CDD), after this period the DHL and CDD groups received successive intraperitoneal injections of streptozotocin (STZ) from 40 to 50mg/kg for 3-5 days. After the induction of diabetes was verified, the animals were kept for another 21 days under these conditions, and then at the end they were euthanized and the muscle was collected. The gastrocnemius muscle was submitted to proteomic analysis. The following comparisons were analyzed: CDD X CND; DHL X CND and DHL X CDD. The functional classification analysis showed three categories with the greatest changes: muscle contraction, energy metabolism and carbohydrate metabolism. The results of the quantitative analysis indicated that the high-fat diet group showed positive regulation of several proteins, indicating a possible adaptive effect triggered by the high-fat diet. The CDD X CND comparison showed predominant negative regulation in the three categories. These results may indicate that muscle function is affected by diabetes and high-fat diet by activating adaptive pathways in the muscle, in addition to identifying the most affected functions. These data have the potential to expand the knowledge we have about diabetes and the mechanisms involved in the pathology.

A diabetes mellitus tipo II é a mais comum, sua prevalência vêm atingindo níveis globais crescentes que demanda um elevado gasto econômico e aumentar a propensão a doenças vasculares, cardíacos e musculares. Neste cenário a proteômica tem potencial de fornecer informações acerca de alterações metabólicas nos portadores pela identificação de vias e possíveis marcadores envolvidos. Assim, o objetivo deste trabalho foi analisar o perfil proteômico do músculo gastrocnêmio de camundongos induzidos a diabetes tipo 2 para identificar alterações e a influência da dieta hiperlipídica . Dezoito camundongos machos adultos foram divididos em 3 grupos experimentais (n=6/grupo) a saber: controle não diabético (CND), diabético induzido por estreptozotocina (CDD) e diabético induzido por estreptozotocina e dieta hiperlipídica (DHL), os mesmos receberam durante 8 semanas dieta hiperlipídica (grupo DHL) ou normocalórica (CND e CDD), após esse período os grupos DHL e CDD receberam sucessivas injeções intraperitoneais de estreptozotocina (STZ) de 40 a 50mg/kg , durante 3-5 dias . Após constatada a indução da diabetes os animais foram mantidos por mais 21 dias nestas condições, e então ao final foram eutanasiados e o músculo foi coletado. O músculo gastrocnêmio foi submetido à análise proteômica. As seguintes comparações foram analisadas: CDD X CND; DHL X CND e DHL X CDD. A análise de classificação funcional mostrou três categorias com maiores alterações: contração muscular, metabolismo energético e metabolismo de carboidratos. Os resultados da análise quantitativa indicaram que o grupo tratado dieta hiperlipídica mostrou regulação positiva de diversas proteínas, indicando um possível efeito adaptativo desencadeado pela dieta hiperlipídica. Já a comparação CDD X CND demonstrou regulação negativa predominante nas três categorias. Estes resultados podem indicar que a função muscular é afetada pela diabetes e pela dieta hiperlipídica pela ativação de vias adaptativas no músculo. Estes dados têm potencial para ampliar o conhecimento que se tem sobre a diabetes e os mecanismos envolvidos na patologia.
Proteomic analysis suggests adaptation of the gastrocnemius muscle of mice with type II diabetes induced by streptozotocin and high-fat diet
Keywords: Skeletal muscle; Proteomics; Diabetes; Músculo esquelético; Proteômica